Permberdayaan Budidaya Ikan Lele dengan Memanfaatkan Teknologi Tepat Guna - Sunaryono Sunaryono; Markus Diantoro; Ahmad Taufiq; Nandang Mufti; Kormil Saputra; Yunan Amza Muhammad (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2021)
Sumbersekar Village is one of the villages in the Malang Regency. The location of this village is very strategic. It is a connecting village between Malang Regency and Batu City because its strategic position makes Sumbersekar Village has a large enough regional potential for its people. One of the potentials that can be developed is the fisheries sector at the Salafiyah Al-Furqan Sumbersekar Islamic Boarding School. The community service program through funding by the State University of Malang aims to maximize the existing potential using appropriate technology. The method to be used is the method of empowering catfish farming by utilizing appropriate engineering technology for alternative energy, catfish farming, and sustainable activities. The activities that will be carried out are assistance, installation of solar cell technology engineering as alternative energy, and construction of catfish farming ponds using a biofloc system. The results of the service activities are expected to become an alternative energy source that can be utilized independently by the Salafiyah Al-Furqan Sumbersekar Islamic Boarding School and used as catfish cultivation with a biofloc system that can develop the abilities and potentials of the residents of the Al-Furqan Salafiyah Islamic Boarding School.